2022
DOI: 10.3390/agronomy12051076
|View full text |Cite
|
Sign up to set email alerts
|

Maize and Wheat Response to Drought Stress under Varied Sulphur Fertilisation

Abstract: This study aimed to examine the influence of long-lasting moderate (45% field water capacity—FWC) and severe (30% FWC) water stress and application of sulphur (elemental sulphur or sulphate) on the growth, yield and mineral composition of wheat and maize. Concentrations of macro- and micronutrients were determined in the aboveground parts of the plants. Drought stress caused a marked decrease in the growth parameters of both plants. Under both optimal water conditions (60% FWC) and moderate water stress (45% F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…Physiologically, this leads to a decline in soil moisture around the roots leading to a decrease in the absorption rate of water and nutrients from the soil sector, which is opposite for N, K, and Zn. These findings are in line with the results observed by Fahad et al (2017), as they reported that drought has declined the uptake of P, leading to a reduction in the relative moisture content of the leaves (Ali and Abdelaal 2020); at par with the increase of the uptake of (N, K, and Zn) (Kulczycki et al 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Physiologically, this leads to a decline in soil moisture around the roots leading to a decrease in the absorption rate of water and nutrients from the soil sector, which is opposite for N, K, and Zn. These findings are in line with the results observed by Fahad et al (2017), as they reported that drought has declined the uptake of P, leading to a reduction in the relative moisture content of the leaves (Ali and Abdelaal 2020); at par with the increase of the uptake of (N, K, and Zn) (Kulczycki et al 2022).…”
Section: Discussionsupporting
confidence: 91%
“…While in terms of morphology, exposure of corn plants to drought contributed to inhibiting plant growth and other vegetative and yield traits. I hypothesized that due to the decrease in levels of leaf extension, cell division, photosynthetic capacity, and enlargement rates, these results are shown by (de Araujo et al (2018), Mi et al (2018), and Kulczycki et al (2022). Furthermore, Kulczycki et al (2022) added, "although corn as another C 4 plant is highly efficient in water use, it remains sensitive to water availability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, planting maize seeds in the fall works in decreasing the growing period which reaches to 100-110 days approximately, conversely planting maize seeds in the spring the growing season reaches 135-140 days. These reasons are accompanied by the self-ability of maize to cope with short periods of water stress resulting in maintaining the yield profitability at acceptable values in the fall, these findings are in harmony with the study of (Kulczycki et al 2022).…”
Section: The Effect Of Water Levelssupporting
confidence: 77%
“…4 a). Furthermore, under this circumstance once Cb becomes beside or in the roots, it works on raising the roots susceptibility to water availability and Cb concentrations 42 . In addition, the reduction of soil moisture decreases the microorganism activity, leading to a decrease in (N, P, Fe, Mn and Cu) and an increase in soil pH.…”
Section: Discussionmentioning
confidence: 99%